Organizing the synchronous remote labworks in institutions of technical engineering education - Sergiy P. Zagorodnyuk; Bogdan B. Sus; Oleksandr S. Bauzha; Valentyna M. Maliarenko (Academy of Cognitive and Natural Sciences, 2023)
This article has been retracted. Please see: Retraction of published article due to the author's proposal - 5 June 2023 Implementation of the synchronous remote labwork system has been discussed in details. Original approach to controlling an arbitrary laboratory devices has been presented. Effective operational interaction system between the teacher and students and complete control over the quality and completeness has been provided. A structure and components of remote labwork that includes microcontroller development board, broadcast imaging device, assistant microcontroller with 4-pole relay have been suggested. A workstation configuration that allow any number of students to remotely connect and operate on the computer was was explained. The mode of coordination of students actions has been discussed. It is shown that in the ideal case, when the program does not need to be corrected and reworked, the student spends ~90% of the time on developing use the working time of computers and in particular the operating time of the specified devices as rationally as possible. Program structure of the additional microcontroller Chipkit that allows the student operate with real laboratory hardware in the mode of synchronous remote laboratory work has been presented.